2020
DOI: 10.1055/s-0040-1713429
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Origins of Endometriosis: Towards Novel Diagnostics and Therapeutics

Abstract: Endometriosis remains an enigmatic disease of unknown etiology, with delayed diagnosis and poor therapeutic options. This review will discuss the cellular, physiological, and genomic evidence of Sampson's hypothesis of retrograde menstruation as a cause of pelvic endometriosis and as the basis of phenotypic heterogeneity of the disease. We postulate that collaborative research at the single cell level focused on unlocking the cellular, physiological, and genomic mechanisms of endometriosis will be accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 129 publications
(161 reference statements)
1
23
0
Order By: Relevance
“…Those epithelial and stromal progenitor cells in adenomyosis then develop independently from the adjacent endometrium basalis once they reside in the myometrium, similar to the development of peritoneal endometriosis, as proposed in a previous study [42]. In a recent report, Filby et al [43] found that the endometrial epithelial progenitors and perivascular mesenchymal stem cells residing in the basalis are highly clonogenic and have multilineage (mesodermal and decidual) differentiation potential. These findings support our view.…”
supporting
confidence: 66%
“…Those epithelial and stromal progenitor cells in adenomyosis then develop independently from the adjacent endometrium basalis once they reside in the myometrium, similar to the development of peritoneal endometriosis, as proposed in a previous study [42]. In a recent report, Filby et al [43] found that the endometrial epithelial progenitors and perivascular mesenchymal stem cells residing in the basalis are highly clonogenic and have multilineage (mesodermal and decidual) differentiation potential. These findings support our view.…”
supporting
confidence: 66%
“…This suggests that the ‘menses-like’ material used to inoculate recipient mice in the DO and DI models may not contain the cell types required to establish chronic or progressive endometriosis. The cellular origins of endometriosis have yet to be fully elucidated ( Filby et al, 2020 ). However, it has been postulated that endometrial stem/progenitor cells are the cells of origin of endometriosis lesions ( Gargett, 2007 ; Cousins et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the number of endometrial cells in the peritoneal fluid does not differ, the cell types contained in the shed tissue may have an important role. Indeed, it has been hypothesized that endometrial epithelial stem/progenitor cells are shed in menstrual fluid which gain access to the peritoneal cavity by retrograde menstruation where they initiate lesions via their clonogenic activity (Gargett, 2007b;Gargett et al, 2016;Cousins et al, 2018a;Filby et al, 2020). Women with endometriosis have more SSEA-1 + SOX9 + epithelial cells in their functionalis compared to normal women.…”
Section: Role Of Stem/progenitor Cells In Endometrial Pathologies-endometriosis and Endometrial Cancermentioning
confidence: 99%